2019
DOI: 10.1007/s11089-019-00875-4
|View full text |Cite
|
Sign up to set email alerts
|

“The Awful Rowing toward God”: Interpretation of Religious Experiences by Individuals with Bipolar Disorder

Abstract: Limited research has been conducted on the religious experiences of people with bipolar disorder (BD). Qualitative research indicates that the disentanglement of pathology and genuine religiosity is an important issue for persons with BD and that some patients experience discrepancy between the explanatory models of mental health care professionals and religious leaders. The current study explores the ways patients with BD interpret religious experiences they have had during illness episodes, how this interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Of the total sample, 50% viewed religiosity in general as an important topic to address in treatment. In a qualitative study preceding the current one (Ouwehand et al 2019b), it was found that not all participants expected mental health care professionals to be equipped to address the issue. To find significance for their often impressive religious experiences, participants sought alternative (spiritual) therapy and training and literature on the Internet, along with standard treatment.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Of the total sample, 50% viewed religiosity in general as an important topic to address in treatment. In a qualitative study preceding the current one (Ouwehand et al 2019b), it was found that not all participants expected mental health care professionals to be equipped to address the issue. To find significance for their often impressive religious experiences, participants sought alternative (spiritual) therapy and training and literature on the Internet, along with standard treatment.…”
Section: Discussionmentioning
confidence: 98%
“…The high involvement in religiosity in the current study can be due to self-selection bias (more religiously interested participants applying than agnostics or atheists). Another explanation could be that high involvement in religiosity is a consequence of the experiences participants had had, especially during mania, which could lead to a religious quest for their significance (Ouwehand et al 2019b) and therefore to more religious involvement. Especially in forms of new spirituality, 'spiritual experiences' and 'spiritual growth' are important issues (De Hart 2011; Heelas et al 2005) and might provide explanatory models for the religious experiences related to BD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations